The Role of the Moral Adviser in Professional Associations - Dion, Gérard (Relations industrielles / Industrial Relations, 1951)
SummaryThe author first outlines the reasons that induce professional associations, who draw inspiration from the Church's doctrine, to take on a moral adviser for their members. However, he points out that socio-economic action, even if it is inspired by the Church's doctrine, is and remains the business of laymen. He then studies the true rôle of the adviser in the employers' and workers' associations, his rights, his duties in the sphere to which he is assigned: this rôle is essentially a sacerdotal one.